The Influence of Understanding Tax Regulations, Taxpayer Awareness and Moral Obligations on Tax Compliance of Four-Wheeled Motor Vehicle Taxpayers - Anisa Jamiatul Fardana (Faculty of Business and Economics , Universitas Yapis Papua, 2025)
This study aims to obtain empirical evidence and analyze the influence of understanding tax regulations, taxpayer awareness, and moral obligations on taxpayer compliance with four-wheeled motor vehicles. This type of research uses hypothesis testing. The research data is primary data obtained directly through field studies using a questionnaire consisting of several statements. The population in this study consisted of motor vehicle taxpayers registered at the Jayapura City SAMSAT Office, with a sample of 100 people. The study results show that understanding tax regulations, taxpayer awareness, and moral obligations significantly positively affect taxpayer compliance at the Jayapura City SAMSAT Office.